DEWI SARASWATI DALAM GAUN MALAM - Wahyu Nur Hidayat; Aan Sudarwanto (Ornamen, 2022)
Dewi Saraswati in this evening gown visualizes the shapes, forms and symbols attached to the figure of Dewi Saraswati into a batik motif which is formed into an evening gown. Dewi Saraswati is the goddes of knowledge or veda. The idea of creation will be focused on (1) how to explore, make sketches, draw designs that come from the shapes, forms and symbols attached to Dewi Saraswati into the new creation batik motifs for evening gown designs? (2) How to create written batik based on a design that has been designed with the motif created by Dewi Saraswati? (3) How are the results of the new batik-patterned fabrics being formed into evening gown? The method used in this approach is to use the creation method which includes the exploration stage, the design stage and the work creation stage. Execution of the process of creating the work The final project is carried out in two stages, namely the batik making process and the evening gown making process. The creation of this work aims to explore the concept of form, appearance, decorative motifs, colors and symbols attached to Dewi Saraswati which is formed into written batik which is then applied to evening gown. The color used for the creation of this final project refers to the color of the Surakarta style batik tradition. The finished batik work is then applied to the evening gown. Evening Gown is a gown worn at night parties with a glamorous look, has sparkling details and is elegantly cut.